Pengembangan Sistem Informasi Pemilihan Kepala Daerah Berbasis Online untuk Meningkatkan Partisipasi Pemilih - Margariti Corlina Inda Liawat; Yulius Nahak Tetik; Katarina Yunita Riti (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
The election of regional heads is a form of democratic implementation that requires the active participation of the community as voters. However, in its implementation, various obstacles are still found such as low voter participation, limited access to information, and lack of efficiency in the conventional voting process. This research aims to develop an online-based regional head election information system as a solution to increase voter participation through the use of digital technology. The research method used is Research and Development (R&D) with a Waterfall system development model which includes the stages of needs analysis, system design, implementation, testing, and evaluation. The developed system provides features of voter registration, candidate information, online voting process, and real-time recapitulation of vote results. The system test is carried out using the Black Box Testing method and shows that all system functions are running according to the user's needs. The results of this study show that the implementation of an online-based election information system can provide easy access, increase transparency, and encourage community involvement, especially young voters, in the process of electing regional heads. Thus, this system has the potential to become a digital innovation that supports improving the quality of local democracy.